2015
DOI: 10.2147/idr.s39186
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the New Delhi metallo-beta-lactamase on beta-lactam antibiotics

Abstract: Since the first New Delhi metallo-beta-lactamase (NDM) report in 2009, NDM has spread globally causing various types of infections. NDM-positive organisms produce in vitro resistance phenotypes to carbapenems and many other antimicrobials. It is thus surprising that the literature examining clinical experiences with NDM does not report corresponding poor clinical outcomes. There are many instances where good clinical outcomes are described, despite a mismatch between administered antimicrobials and resistant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 61 publications
3
14
0
Order By: Relevance
“…Recently, Ghazi and colleagues (124) observed that despite a high MIC indicative of meropenem resistance due to Verona integrin-encoded metallo-betalactamase (VIM) in Enterobacteriaceae, treatment with this antibiotic resulted in unexpected bactericidal activity when used in a humanized high-dose regimen in a murine infection model. Additional examples with gram-negative bacteria harboring the New Delhi metallo-beta-lactamase (NDM) have also been published and supported by a review of the clinical literature surrounding successful treatment with carbapenems for NDM infections (125).…”
Section: Beyond the Mic: Genotypic Profilingmentioning
confidence: 98%
“…Recently, Ghazi and colleagues (124) observed that despite a high MIC indicative of meropenem resistance due to Verona integrin-encoded metallo-betalactamase (VIM) in Enterobacteriaceae, treatment with this antibiotic resulted in unexpected bactericidal activity when used in a humanized high-dose regimen in a murine infection model. Additional examples with gram-negative bacteria harboring the New Delhi metallo-beta-lactamase (NDM) have also been published and supported by a review of the clinical literature surrounding successful treatment with carbapenems for NDM infections (125).…”
Section: Beyond the Mic: Genotypic Profilingmentioning
confidence: 98%
“…NDM is endemic to parts of Asia and is responsible for sporadic outbreaks around the globe [Zmarlicka 2015]. As of August 2016 when we accessed the NCBI database, 16 variants of NDM were identified on a variety of plasmid types, corresponding to the high diversity of Enterobacteriaceae species shown to express it [NCBI 2016, Zmarlicka 2015].…”
Section: Ndmmentioning
confidence: 99%
“…As of August 2016 when we accessed the NCBI database, 16 variants of NDM were identified on a variety of plasmid types, corresponding to the high diversity of Enterobacteriaceae species shown to express it [NCBI 2016, Zmarlicka 2015]. A comprehensive study from 2012 to 2014 of 38,266 Enterobacteriaceae isolates collected from 40 countries spanning every inhabited continent found that global incidence of MBL presence is low (0.5%, 163/38,266), but dissemination is high (85%, 34/40 countries).…”
Section: Ndmmentioning
confidence: 99%
“…Meropenem was also more efficacious against UNT184-1 despite having the same MIC against both strains. A similar observation was made of increased in vivo susceptibility compared with in vitro activity against NDM-1-expressing isolates (21). A reason behind these differences may be reduced expression of activity of the enzyme in vivo due to metal ion availability, thus accounting for greater observed efficacy of certain treatments.…”
mentioning
confidence: 52%